The Inhibitory Effect of Recombinant Human Soluble Thrombomodulin on Initiation and Extension of Coagulation - Mohri, Mitsunobu; Sugimoto, Emika; Sata, Minako; Asano, Toshio (Thrombosis and Haemostasis, 1999)
Recombinant human soluble thrombomodulin (rhsTM) was compared with various anticoagulants for in vitro anticoagulant effects on thrombin generation, clotting time, and thromboelastography. rhsTM as well as APC reduced the level of the peak of the thrombin generation curve, but we did not observe any time-delay to reach the peak. This effect of rhsTM was diminished in PC-deficient plasma and was closely associated with the inhibitory effect on prothrombinase and factor Va. On the other hand, hirudin and argatroban delayed the time to reach the level of the peak, without reducing it. rhsTM and other anticoagulants except for activated protein C (APC) were found to have concentration-dependent anticoagulant activity by conventional clotting tests. However, the concentration of rhsTM for clotting time was slightly affected by anti-protein C antibody. Moreover, the concentration of rhsTM required to inhibit thrombin activity directly was 50 times higher than that needed to inhibit thrombin generation. The effect of rhsTM on clot development was compared with that of other anticoagulants by thromboelastography; rhsTM reduced the growth of the clot but had little effect on the time to activate clotting, while the other anticoagulants had the opposite effect. This effect of rhsTM was completely abolished by the addition of anti-protein C or anti-protein S antibody.These findings suggest that rhsTM attenuates blood clotting by reducing the level of generated thrombin through protein C activation and subsequent factor Va inactivation and prothrombinase inhibition.
Keywords: Soluble thrombomodulin; thrombin generation; thromboelastography; activated protein C; argatroban; hirudin; heparin